Peace like a river ebook - Enger, Leif (2023)
A boy searches for his fugitive brother in 1960s Minnesota in this New York Times bestseller—“a stunning debut novel [of] faith, miracles, and family” ( Publishers Weekly , starred review). An eleven-year-old asthmatic boy, Reuben Land has reason to believe in miracles. But he will soon learn that life, even when touched by the divine, is never easy. Along with his father and poetically inclined sister, Reuben finds himself on a cross-country search for his outlaw older brother who has been controversially charged with murder. The Land family’s journey is touched by serendipity and the kindness of strangers, and its remarkable conclusion demonstrates how family, love, and faith can stand up to the most terrifying of enemies—and the most tragic of fates. “A rich mixture of adventure, tragedy, and healing,” Peace Like a River is “a collage of legends from sources sacred and profane—from the Old Testament to the Old West, from the Gospels to police dramas” (Ron Charles, The Christian Science Monitor ).